Embryonic and postnatal telomere length decrease with ovulation order within clutches - Noguera, José C. (Sci Rep, 2016)
Telomere length (TL) in early life has been found to be predictive of subsequent lifespan. Factors such as parental TL, parental age and environmental conditions during development have been shown to contribute to the observed variation in TL among individuals. One factor that has not hitherto been considered is ovulation order, although it is well established that the last hatched/born offspring in a brood or litter often show relatively poor subsequent performance. We examined the within- and across-clutch effect of ovulation order on TL in embryos of zebra finches experiencing the same controlled incubation conditions (N = 151), and tested whether any such ovulation order effects remained detectable in adults (N = 122). Irrespective of clutch and egg size, TL in early-stage embryos (72 h incubation) markedly decreased with within-clutch ovulation order; the difference in TL of first and last-laid embryos was equivalent to the average within-individual telomere loss over the entire period of nestling and juvenile life. This ovulation-order effect occurred only within but not across clutches, and was still evident in adults. Given that TL in early life predicts lifespan, our results suggest that parental effects on telomere length could contribute to the known poor performance of later-ovulated family members.